2019
DOI: 10.1002/jcla.22839
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio can specifically predict the severity of hypertriglyceridemia‐induced acute pancreatitis compared with white blood cell

Abstract: Objectives We aimed to evaluate the values of neutrophil‐to‐lymphocyte ratio (NLR) and white blood cell (WBC) in predicting severity of acute pancreatitis (AP) with different etiologies. Methods We compared NLR and WBC levels in patients with different etiologies and AP severity. The optimal cutoff value for them to predict severe acute pancreatitis (SAP) was determined by receiver operating characteristic (ROC) curve analysis. Results Both NLR and WBC were elevated in patients with SAP. After subgrouping AP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…[ 23 ] Furthermore, neutrophils are useful for immune monitoring and assessment of prognosis in patients with some tumors (eg, kidney cancer, lung cancer, and gastrointestinal stromal tumors). [ 3 , 23 ] In addition, the NLR can predict the severity of hypertriglyceridemia-induced acute pancreatitis, whereas the WBC is less predictive [ 2 ] ; the NLR also can aid in the diagnosis of ankylosing spondylitis and prognostic assessment of cancers such as renal cell carcinoma. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Furthermore, neutrophils are useful for immune monitoring and assessment of prognosis in patients with some tumors (eg, kidney cancer, lung cancer, and gastrointestinal stromal tumors). [ 3 , 23 ] In addition, the NLR can predict the severity of hypertriglyceridemia-induced acute pancreatitis, whereas the WBC is less predictive [ 2 ] ; the NLR also can aid in the diagnosis of ankylosing spondylitis and prognostic assessment of cancers such as renal cell carcinoma. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, total WBC and percentages of differential WBCs are included in the diagnostic evaluation of suspected appendicitis or acute pancreatitis. [ 2 , 3 ] Also, new findings suggest that lymphocyte changes in patients with 2019 novel coronavirus (COVID-19) should be carefully monitored. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, increasing studies have reported that many blood routine examination‐derived biomarkers, such as NLR, PLR, and LMR, whose levels could be closely related to systemic inflammation and immune response status . These biomarkers are proved to be well associated with various infectious diseases, oncological diseases and autoimmune diseases . In recent years, following NLR, PLR, and LMR, SII has been discovered as an emerging indicator for these diseases and shed great predictive and diagnostic potential .…”
Section: Discussionmentioning
confidence: 99%
“…Acute systemic inflammatory responses have been associated with changes in neutrophilia and lymphocytopenia, which reflects dramatic changes in the immune system in the AP environment [12]. And NLR represents a balance between inflammatory activator neutrophils and inflammatory regulator lymphocytes, and the higher the value, the more unbalanced the inflammatory state [18,19]. Among many inflammatory markers, an elevated NLR is a reliable and sensitive inflammatory marker that can be a valuable predictor of poor outcomes in patients with infection, sepsis, stroke, cardiovascular disease, and cancer [20].…”
Section: Disease Markersmentioning
confidence: 99%
“…At the same time, a growing number of studies have shown that NLR is associated with AP and is better than other serum markers in predicting the severity and prognosis of AP [9]. Huang et al demonstrated that NLR is more sensitive and accurate than WBC in determining the severity of HTG-AP [18]. Abayli and Gencdal conducted a correlation study between the NLR and Ranson score on 435 AP patients and found that NLR is a simpler, more practical, and effective parameter for diagnosing the severity of AP compared with the current scoring system [22].…”
Section: Disease Markersmentioning
confidence: 99%